THE ECONOMIC CONTENT OF THE FORMATION OF COMMODITY PORTFOLIO - A. M. Libo (Модернизация, инновация, развитие, 2016)
The article provides a portfolio of marketable concept, examines the main stages in the formation of commodity portfolio, given the characteristics of commodity policies and strategies of the enterprise.